(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
To predict exact age of injury always remains a puzzle in the medical field because of wide range of variability occurring grossly during their healing process.1 Dating of an injury both in living and dead is of crucial medico legal issue in the field of crime investigation to fix the responsibility. A doctor is required to mention the age of injury specifically and individually while certifying an injury2. To determine the age of injuries is one of the most important aspect in clinical forensic medicine work because this aspect is related to time of occurrence of the crime. To know the time of certain events e.g. accidents, quarrels is of vital importance in the reconstruction of the chain of events. Filling the blanks of time gap helps the investing police officer to come to the facts and can also make conclusion whether the injuries are as a result of single or split events.3 After taking into consideration the importance of age of injury, it was decided to study to estimate age of mechanical injuries in hospitalized cases, at tertiary care centre.